Preparation of Polyurethane-Modified Epoxy Coating Materials Based on Vegetable Oil Derivated Ester - Ghozali, Muhammad; Restu, Witta Kartika; Triwulandari, Evi; Fauzi, Lutfi Rizky (Jurnal Sains Materi Indonesia, 2023)
This study utilize vegetable oil derivatives as a polyol in polyurethane. A modification of epoxy using polyurethane was done using ester derivative of vegetable oils as polyols, which was polyethylene glycol monooleate (PEGMO). The PEGMO was synthesized via an esterification reaction. The synthesis of polyurethane-modified epoxy using polyethylene glycol monooleate ester (PME-PEGMO) was conducted by reacting epoxy, tolonate and PEGMO. Analysis results of FTIR and H-NMR showed a new absorption peak derived from the urethane bond. The mechanical and thermal properties were characterized by a universal testing machine (UTM) and thermogravimetry analysis (TGA), respectively. According to the analysis results, it is shown that the addition of polyethylene glycol monooleate ester-based polyurethane on epoxy improved the mechanical properties of the epoxy, from 69.61 kgf/cm2 to139.80 kgf/cm2. However, it decreased the thermal stability of the epoxy. At 500°C, the mass of epoxy was remaining 28%, while the PME-PEGMO was only 13%.